INFLUENCE OF ALBIT ON THE STRUCTURE AND PRODUCTIVITY OF THE SEED PLANT OF TABLE BEET - V.I. Gryazeva (Volga Region Farmland, 2019)
Seed quality is one of the most important factors for obtaining a good harvest. Difficulty is in the reproduction of seeds of cross-pollinated biennial plants, which is beetroot. The main goal in its seed production is the maintenance of economically valuable traits of populations. The effect of Albit on the structure and productivity of the seed plant of table beet was studied in Penza region. It was established that the seed ripening period in all variants of treatment with albite was shorter than in the control by 4–9 days. In most variants, on average over two years, the highest seed productivity was observed in the seed-bearing plants of the III-IV branching types. Type I seed plants are less productive, but their seeds are larger and have better sowing qualities. The greatest number of seeds from a plant was formed in all variants of the seed-bearing plants of the III-IV branching types. The same trend is observed in the variants of the experiment with Albit. More branched seed-bearing plants are more productive than less branched ones. So, during treatment in the budding phase, type III-IV type seed-bearing plants formed 127.5 grams, while 118.0 grams of type I seed-bearing plants. After treatment during the flowering phase, multiramouse seed-bearing plants are 11.5 grams more productive than the subramous. The treatment of seed plants of table beet with Albit contributed to an increase in the mass of 1000 seedballs in an average of 1.5-2.1 grams. Studies have shown that there is a matricular heterogeneity, which is a consequence of differences in the location of seeds on the mother plant. The best quality seeds are formed on the central axis, and the worst – on second order rosette shoots.